European integration, 1950-2003 : superstate or new market economy? - Gillingham, John (Cambridge Univ. P. CambridgeGB, 2003)
Describes the origins of European integration at the levels of ideas and institutions - as well as the institutionalization of integration - against a backdrop of the German 'economic miracle'. Focuses on the watershed event of the era, the regime change. Describes the most dynamic period in the history of European integration - 1980s. Looks at the uneasy standoff of events reached in the 1990s. Examines the development of community institutions, the relationship between member-states and Brussels, eastern expansion and the present economic challenges facing the EU.